Between the Autonomy and the Autarchy of the National Jury of Elections: The Irreversibility of its Decisions in the Jurisdictional Venue in Question - Donayre Montesinos, Christian (2006)
The Peruvian legal system includes two autonomous institutions: the National Election Jury and the Constitutional Court. However, the Act 28642, approved by the Peruvian Parliament and supported by the electoral entity, prevents constitutional processes from being initiated against decisions made by the latter. The author suggests that this situation could lead to scenarios of autarchy, where the JNE acts without supervision, what affects the balance between powers. In this framework, the author proposes analyzing the problem from the general theory of constitutionally autonomous agencies. This paper aims to establish that although agencies are autonomous, they cannot remain completely disconnected from each other. Therefore, mechanisms must be created to allow for a relationship between them while avoiding autarkic scenarios without control.